Corpus-based Voyant Tools for Teaching IELTS Writing: Design and Implementation - Ramadhani, Dwiansari (English Education Department at FKIP Nommensen University, 2025)
This conceptual paper aims to present practical guidelines for integrating Voyant Tools into the design of IELTS writing classes, particularly in the English as a Foreign Language (EFL) context. The paper adopts a tool-application demonstration approach to propose instructional steps, drawing on a synthesis of literature in corpus linguistics in EFL teaching, Voyant Tools for writing, and Voyant Tools for teaching IELTS writing, which becomes the theoretical foundation of the practice. The method involves introducing Voyant Tools’ interface and key functions, fetching data, selecting keywords, and applying the tool in classroom instruction. The proposed procedure highlights how Voyant Tools can serve as a valuable solution to expose learners to authentic language patterns and enhance their awareness of academic writing style, thereby contributing to their improved writing performance. This approach has implications for EFL instructors to seek more accessible, corpus-based teaching methods and for researchers exploring digital tools in language education. It is recommended that more educators, as well as students, incorporate similar tools in other areas of language skills. The limitation of this paper is acknowledged regarding the absence of empirical classroom testing across more varied learner backgrounds.